Urban tourism - Page, Stephen, 1963- (London ; New York : Routledge, 1995)
This is the first introductory level text to look at the nature of urban tourism. A study of the issues and problems involved in urban tourism reveals the multifunctional nature of cities as tourist destinations. All the main aspects of urban tourism are examined including: the range of tourists and their motives for visiting urban destinations, the types of facilities, the impact of tourism on urban environments, and managerial and planning techniques used to market and manage cities as tourism destinations. Recent innovations in the management of urban tourism are highlighted. A range of international case studies provide practical examples of the issues raised. This integrated, holistic view of urban tourism encompasses the needs of practitioners, and will be very useful for students of tourism, leisure and planning at diploma and undergraduate level.
Kniha patří k raným systematickým pracím věnujícím se městskému turismu jako samostatnému fenoménu. Autor analyzuje, jak města fungují jako turistické destinace, jaké produkty a zážitky nabízejí a jaký ekonomický, sociální a prostorový dopad má cestovní ruch na jejich rozvoj. Page představuje hlavní typy městských atraktivit (kulturní dědictví, architektura, události, nakupování), popisuje strukturu městské turistiky a zkoumá vztah mezi plánováním města a strategií cestovního ruchu. Publikace poskytuje základní teoretický rámec pro pochopení toho, proč se města stávají klíčovými uzly turismu a jak lze tento potenciál řízeně rozvíjet.
Rejstř.
Bibliogr.
Keywords: cestovní ruch; města; městská turistika; monografie; tourism; cities and towns; monographs